Визуализация данных МТЗ по способу скалярных импедансов для численных моделей элементарных проводящих структур - Причепий, Т.И. (Геофизический журнал, 2014)
Проаналізовано можливість та особливості застосування методу скалярних імпедансів з метою візуалізації результатів МТЗ на прикладі елементарних структур, для яких за програмою 3D моделювання обчислено значення аномального електромагнітного поля. Наведено графічні еквіваленти модулів скалярних параметрів імпедансного типу |ξ | та |ζ|, обраховані для вказаних моделей. Розглянуто їх характерні риси для різних типів провідних структур. The work is devoted to the analysis of a possibility and traits of use of the method of scalar impedances for the purpose of visualizing the results of MTS. It is made by the example of a number of elementary structures, for which the values of anomalously electromagnetic field was calculated by the program of 3D modeling. Graphic equivalents of modules of scalar parameters of impedance type ξ and ζ , designed for the given models are resulted, their characteristic features for various types of conducting structures are considered.